2009
DOI: 10.1124/jpet.109.155770
|View full text |Cite
|
Sign up to set email alerts
|

Extended Methamphetamine Self-Administration in Rats Results in a Selective Reduction of Dopamine Transporter Levels in the Prefrontal Cortex and Dorsal Striatum Not Accompanied by Marked Monoaminergic Depletion

Abstract: Chronic abuse of methamphetamine leads to cognitive dysfunction and high rates of relapse, paralleled by significant changes of brain dopamine and serotonin neurotransmission. Previously, we found that rats with extended access to methamphetamine self-administration displayed enhanced methamphetamine-primed reinstatement of drug-seeking and cognitive deficits relative to limited access animals. The present study investigated whether extended access to methamphetamine self-administration produced abnormalities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
127
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(156 citation statements)
references
References 41 publications
27
127
2
Order By: Relevance
“…Furthermore, and in contrast to effects of binge METH treatment (Hadlock et al, 2010), no increases in GFAP immunoreactivity, a marker of astrocytic activation and neuronal damage, were found after METH self-administration. This is consistent with previous reports that indicate self-administration produces adaptations that differ from the effects of binge METH treatment (Schwendt et al, 2009;Brennan et al, 2010).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Furthermore, and in contrast to effects of binge METH treatment (Hadlock et al, 2010), no increases in GFAP immunoreactivity, a marker of astrocytic activation and neuronal damage, were found after METH self-administration. This is consistent with previous reports that indicate self-administration produces adaptations that differ from the effects of binge METH treatment (Schwendt et al, 2009;Brennan et al, 2010).…”
Section: Discussionsupporting
confidence: 82%
“…The findings of the current study are generally consistent with the neuroadaptations reported in Schwendt et al (2009) after METH self-administration. In particular, METH exposure persistently decreased DAT, without altering GFAP, TH, or VMAT-2 immunoreactivity in the striatum.…”
Section: Meth Self-administration Dat 301supporting
confidence: 81%
See 2 more Smart Citations
“…However, there exists a large literature indicating methamphetamineglutamate interactions in mediating high-dose methamphetamine-induced neuronal toxicity within the forebrain (Abekawa et al, 1994;Battaglia et al, 2002;Burrows et al, 2000;Davidson et al, 2007;Golembiowska et al, 2003;Marshall et al, 1993;Simões et al, 2007Simões et al, , 2008Sonsalla et al, 1989;Tata and Yamamoto, 2007). Although these latter studies are relevant to cellular processes induced by very heavy methamphetamine use, they fail to assess the potential role for glutamate in the establishment of methamphetamine self-administration when drug intake is relatively low (eg, Gass et al, 2009;Schwendt et al, 2009;Shepard et al, 2006, Stefanski et al, 1999). …”
Section: Introductionmentioning
confidence: 99%